Public Policies and Companies Recovered by their Workers in Argentina. Analysis of the Worker Self-Management Program, 2004-2012 - Hudson, Juan Pablo (2016)
This article explores the complex relationship between the companies recovered by their workers in Argentina and the state during the last decade through an analysis of the evolution of Ministry of Labor, Employment, and Social Security policies regarding these self-management experiences. A central conclusion of this study is that Argentine governments since 2003, after the serious social, political, and economic crises resulting from the systematic application of neoliberal policies, had to progressively incorporate the various forms of self- organization that were created and consolidated by social movements such as the recovered companies.